A framework of indicators for assessing construction automation and robotics in the sustainability context. (1st May 2018) - Pan, Mi; Linner, Thomas; Pan, Wei; Cheng, Huimin; Bock, Thomas
Abstract: "Building production" technology, i.e. construction automation and robotics (CAR), is on a worldwide level increasingly recognized as stating a key element of the future of construction, although CAR up to date has never experienced large-scale real-world implementation. However, the recent significantly growing demand for sustainability has the potential to serve as the necessitated trigger for CAR's large-scale deployment. In that context, systematic guidance for the construction industry is however missing, and there have been limited attempts to thoroughly investigate the impacts of utilizing CAR with regard to the sustainability performance of construction and buildings. The research presented in this paper makes a first step to fill this research gap by reviewing and investigating the available CAR strategies and technologies and developing for the first time a consistent framework of indicators for assessing the sustainability performance of utilizing CAR for buildings. The overall goal of the research is to develop, through this framework, a robust and reliable assessment method that can be used in the industrial context to assess the sustainability of building construction projects that consider using CAR. Beyond the development of the indicator framework, the research plan adopting the V-Model approach foresees to translate the framework into an assessment method which will then in several iteration cycles be verified and validated in real world. Highlights: Change of the notion of "construction" to that of "building production". Sustainability is a driver for large-scale use of construction automation robotics. CARSAM is developed to assess sustainability of construction automation robotics. A system engineering approach is suggested to enforce liability of the framework.